The last Olympian - Riordan, Rick. (New York : Disney/Hyperion Books, 2009)
The long-awaited prophecy surrounding Percy Jackson's sixteenth birthday unfolds as he leads an army of young demigods to stop Kronos in his advance on New York City, while the Olympians struggle to contain the rampaging monster, Typhon.
School Library Journal, June 2009
Booklist starred, May 2009
Publisher's Weekly, May 2009
Kirkus Starred, May 2009
New York Times, May 2009
Horn Book, October 2009
Keywords: Mythology, Greek -- Juvenile fiction; Fate and fatalism -- Juvenile fiction; Monsters -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Titans (Mythology) -- Juvenile fiction; Mythology, Greek -- Fiction; Fate and fatalism -- Fiction; Monsters -- Fiction; Animals, Mythical -- Fiction; Titans (Mythology) -- Fiction; Fantasy; Greek mythology -- Fiction; Fate and fatalism -- Fiction; Monsters -- Fiction; Mythical animals -- Fiction; Titans (Mythology) -- Fiction; Fantasy fiction; Fantasy fiction